Konsep Ulul Albab dalam Kajian Tafsir Tematik - Mahmuda, Imaniar (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2018)
The article takes the study of Ulul Albab based on The Holly Qur’an’s definition and spiritual base. It draws a conclusion that in The Holly Qur’an, Ulul Albab covers three meanings : dzikir, thinking, good deeds. This, in detail, is an ability to contemplate natural and social phenomenas. The Ulul Albab citation could be achieved only by good thinkers of themselves, natural and life phenomenas. This could invite a strong Islamic culture integrating the substance of divinity and logical values that position Islam as the supreme icon of world civilization for hundreds years ever. Keywords : Ulul Albab in The Holy Qur’an